Detection of Candida spp. from mastitis cattle milk and study of the antifungal activity of ketoconazole-loaded solid lipid nanoparticles and nanostructured lipid carriers against Candida isolates - Isa Swadi Touhali,; Khairi Jameel Al Ruaby,; Alwan Al Qushawi, (Journal of the Pakistan Medical Association, 2023)
Objective: To isolate candida species from cattle milk isolates and investigate the advances of ketoconazole-loaded solid lipid nanoparticles and ketoconazole-nanostructured lipid carters, and to analyse their properties and compare their antifungal performance compared to free ketoconazole. Method: The cross-sectional study was conducted from October 2021 to April 2022 in Waist Governorate of Iraq, and comprised milk samples obtained from cows infected with mastitis. The study was initiated after obtaining approval from the IRB of the veterinary hospital in the Governorate of Iraq. The samples were cultured on 4% savoured dextrose agar and incubated independently at 37°C before they were subjected to a range of tests. Mastitis was checked with a commercially available cultural and morphological identity card system and through candida chromogenic agar. The data was analyzed by using the programmed SPSS IBM version 20. The chi-square test was used to check the inhibition zones due to the anti-fungal activity of KTZ-LPN and free KTZ. The significance level was kept at p<0.05. Results:Of the 225 samples, 116(51.5%) were obtained from cows infected with mastitis on the basis of a commercially available cultural and morphological identity card system. Among the 61(52.6%) candida albicans isolated, resistance to amphotericin B was shown by 60(98%) and to nystatin by 58(95%), while those sensitive to ketoconazole were 32(52%) and to fluconazole 31(51%).The ketoconazole nanostructured lipid nanoparticle (KTZ-NLC) preparations showed higher antifungal activity than other tested preparations at 0.25ug/ml with a minimum inhibition zone of 15±2.4 mm followed by ketoconazole solid lipid nanoparticle (KTZ-SLN) preparations with minimum inhibition zone of 15±1.3 mm. Free ketoconazole showed the lowest inhibition zone values at the same concentration (0.25ug/ml), which was 11±1.3 mm. Both these lipid nanoparticles formulations, especially ketoconazole nanostructured lipid carriers (KTZ-NLC), could represent a promising formulation for antifungal application and use. Conclusions: Ketoconazole-nanostructured lipid carter formulations were found to be effective for drug delivery. Keywords: Nanoparticles, Fluconazole, Amphotericin, Ketoconazole, Nystatin, Drug, Milk, Candida, Mastitis.